2006
DOI: 10.1136/bjsm.2005.022889
|View full text |Cite
|
Sign up to set email alerts
|

Sports injuries: population based representative data on incidence, diagnosis, sequelae, and high risk groups

Abstract: Future injury prevention measures should focus on the high risk group of young male recreational athletes. The data indicate that the fear of damage to health and injury, believed to be significant internal psychological barriers to participation in sports, is largely unwarranted for the female population and/or older age groups. Sporting injuries are a marginal phenomenon among the female population and mobile seniors actively engaged in sports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
2
13

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 28 publications
5
76
2
13
Order By: Relevance
“…We found that age was not significantly associated with the history or severity of injuries contrary to the findings of Schneider et al [9], who reported that the incidence of sports injuries declined noticeably in older age groups. This discrepancy could be a result of differences in the samples of our study and theirs, which included male and female adults aged 18-79 years of age, and was not restricted to professional athletes.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…We found that age was not significantly associated with the history or severity of injuries contrary to the findings of Schneider et al [9], who reported that the incidence of sports injuries declined noticeably in older age groups. This discrepancy could be a result of differences in the samples of our study and theirs, which included male and female adults aged 18-79 years of age, and was not restricted to professional athletes.…”
Section: Discussioncontrasting
confidence: 57%
“…These variables were included in the regression model because some of them were found to be significant in the crude analyses and others were found to be associated with sports injuries in previous studies [2,3,4,5,6,7,9,10,11]. For both outcome variables, age and type of sport were considered as the most important associated factors.…”
Section: Methodsmentioning
confidence: 99%
“…Además, los lapsos de lesiones o días de enfermedad en los practicantes no presenta inclinaciones hacia ningún periodo de tiempo en particular, significando que los episodios en los jóvenes son similares, aunque otros autores como Schneider et al (2006) encuentran que el promedio de inhabilidad son catorce días.…”
Section: Correlatos Asociados Con La Práctica De Actividad Físico-depunclassified
“…A prática de exercícios de alta intensidade no esporte de rendimento está relacionada ao acometimento de estresse e traumas corporais e psicológicos (WIESE-BJORNSTAL, 2010). No contexto esportivo, a dor física pode suceder das lesões traumáticas ou não-traumáticas, sendo classificadas como torção, distensão, luxação, contusão, fadiga ou fratura, e que atingem músculos, ossos e articulações (PETERSON, 2002;SCHNEIDER et. al.…”
Section: Introductionunclassified